Beyond Medical Bureaucracy: an Inquiry into Women’s Right to Abortion in Italy - Chiara Quagliariello (Antropologia)
Women’s right to abortion has been questioned over the past few decades, in tandem with the increasing number of doctors who refuse to perform the procedure in Italian public hospitals. In this paper I argue that even when there is no conscience-based refusal by health professionals, other factors can hinder women’s access to legal abortion. My study focuses on three aspects of the medical assistance offered to women who desire or who need to end their pregnancy: (i) the obligation for doctors to provide information and ask for informed consent from patients before the abortion procedure can take place; (ii) the growing presence of men, such as women’s partners, during medical consultations related to abortion; and (iii) the growing influence of psychological consultations before and after abortion. Starting from the findings of long-term ethnographic work in Italy, I examine to what extent these elements play a role in therapeutic and non-therapeutic abortion, and according to women’s social profile.